2005
DOI: 10.1007/s10722-004-1932-7
|View full text |Cite
|
Sign up to set email alerts
|

New Wild Lactuca Genetic Resources with Resistance Against Bremia lactucae

Abstract: A total of 1027 genotypes of wild Lactuca spp. (L. serriola, L. saligna, and L. aculeata), originating from Israel, Jordan, East Turkey, Armenia, Kazakhstan, China, and various other countries in Europe were screened for resistance to the lettuce downy mildew (Bremia lactucae Regel). The genotypes of L. serriola (N = 962); L. saligna (N = 43); and L. aculeata (N = 22) were tested at the seedling stage with two isolates of B. lactucae (race Bl-21 and Isr-74) isolated from cultivated lettuce in Italy and Israel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 30 publications
3
21
0
1
Order By: Relevance
“…In this study, all resistant accessions were characterized by some degree of haustorial formation, at a level significantly different from the compatible controls (Table 5), the exception again being L. saligna, where development of haustoria was not recorded. The existence of qualitative as well as quantitative resistance in L. saligna is expected (Jeuken and Lindhout, 2002;Lebeda et al, 2002;Beharav et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, all resistant accessions were characterized by some degree of haustorial formation, at a level significantly different from the compatible controls (Table 5), the exception again being L. saligna, where development of haustoria was not recorded. The existence of qualitative as well as quantitative resistance in L. saligna is expected (Jeuken and Lindhout, 2002;Lebeda et al, 2002;Beharav et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The latter approach would be particularly effective if the different Rfactors determined different resistance mechanisms. The exploitation and utilization in lettuce breeding of wild Lactuca germplasm offers a source of resistance genes which may determine different resistance mechanisms Beharav et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many other sources of resistance have been identified in germplasm screens but have yet to be characterized genetically (e.g. Bonnier et al 1994;Lebeda and Zinkernagel 2003;Beharav et al 2006). As more resistance genes are characterized from these and other sources, it is likely that several hundred genes with efficacy against B. lactucae will be identified that will require a coordinated, rational nomination process.…”
Section: Introductionmentioning
confidence: 99%
“…The wild and cultivated lettuces are sexually compatible and lettuce geneticists and breeders have made extensive use of this wild species, mainly for disease resistance, including resistance against downy mildew caused by Bremia lactucae (Crute 1992;Lebeda et al 2002;Beharav et al 2006). At least eight functional resistance genes (R-genes) with different specificities against downy mildew have been mapped to the RGC2 cluster, the major cluster of R-genes in lettuce (Farrara et al 1987;Kesseli et al 1994).…”
mentioning
confidence: 99%